Comprehensive backscattering characteristics analysis for quantitative ultrasound with an annular array: a basic study on homogeneous scattering phantom. (13th June 2019) - Mizoguchi, Takeru; Tamura, Kazuki; Mamou, Jonathan; Ketterling, Jeffrey A.; Yoshida, Kenji; Yamaguchi, Tadashi
Abstract: High-frequency ultrasound (HFU, >20 MHz) and quantitative ultrasound (QUS) methods permit a means to understand the relationship between anatomical and acoustic characteristics. In our previous research, we showed that analyzing the acoustic scattering with HFU was an effective method for noninvasive diagnosis. However, the depth of field (DOF) of HFU transducers was limited, which constrains the range of QUS analysis. In this study, we seek to improve the accuracy of HFU, QUS-based parameters on the envelope statistics and frequency-based analysis by using an annular array that allows for an extended DOF. A 20-MHz annular-array transducer with five elements was employed to obtain signals which were beamformed in post-processing. Two kinds of low concentration scattering phantoms were scanned with 30- μ m step size. Two QUS analysis techniques were employed: the Nakagami distribution and the reflector method. The results demonstrated that the annular array provides a stable analysis over an extended axial range.